2018
DOI: 10.1177/0013164418806694
|View full text |Cite
|
Sign up to set email alerts
|

The Bayesian Multilevel Trifactor Item Response Theory Model

Abstract: Advancements in item response theory (IRT) have led to models for dual dependence, which control for cluster and method effects during a psychometric analysis. Currently, however, this class of models does not include one that controls for when the method effects stem from two method sources in which one source functions differently across the aspects of another source (i.e., a nested method-source interaction). For this study, then, a Bayesian IRT model is proposed, one that accounts for such interaction amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Research has demonstrated the value of using informative priors with Bayesian models when working with small samples. One simulation study showed that a sample size of 250 was sufficient to obtain accurate parameter estimates when informative prior distributions were assigned to the parameters of a Bayesian multilevel trifactor IRT model specified with eight orthogonal dimensions (Fujimoto, 2019). Another simulation study found that a sample size of 200 was enough to obtain accurate parameter estimates when informative priors were used with Bayesian multilevel structural equation models specified with four dimensions (Depaoli & Clifton, 2015; Holtmann, Koch, Lochner, & Eid, 2016).…”
Section: Sample Size Requirements For Multidimensional Item Response mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated the value of using informative priors with Bayesian models when working with small samples. One simulation study showed that a sample size of 250 was sufficient to obtain accurate parameter estimates when informative prior distributions were assigned to the parameters of a Bayesian multilevel trifactor IRT model specified with eight orthogonal dimensions (Fujimoto, 2019). Another simulation study found that a sample size of 200 was enough to obtain accurate parameter estimates when informative priors were used with Bayesian multilevel structural equation models specified with four dimensions (Depaoli & Clifton, 2015; Holtmann, Koch, Lochner, & Eid, 2016).…”
Section: Sample Size Requirements For Multidimensional Item Response mentioning
confidence: 99%
“…The previously described MRQ data were analyzed to illustrate that the simulation results from the two-tier dimensional condition related to smaller sample sizes are relevant to real settings. Data were obtained from 121 students (in Grades 6-8); in-depth details of the characteristics of the sample are in Neugebauer and Fujimoto (2019). The two-tier structure hypothesized for the data was composed of primary dimensions of intrinsic and extrinsic motivation and secondary dimensions of challenge (five items), curiosity (four items), involvement (six items), competition in reading (six items), recognition in reading (four items), and grades (four items).…”
Section: Illustration With Real Datamentioning
confidence: 99%
“…Nevertheless, the performance of the LPML has been investigated in multidimensional situations. In simulation studies in which nested-dimensionality IRT models (e.g., a bifactor IRT model) and constrained (or more parsimonious) variations of those nested-dimensionality models (e.g., a testlet IRT model) were being compared, with these studies having conditions in which each type of model was the true model, the LPML consistently identified the correct model (Fujimoto, 2018(Fujimoto, , 2019(Fujimoto, , 2020Li et al, 2006). In other words, in these studies, the LPML did not consistently favor the more complex models like the DIC.…”
Section: Log-predicted Marginal Likelihoodmentioning
confidence: 99%
“…If the primary dimension is only weakly represented in the data, then a structure other than a bifactor structure would be more appropriate for the data. The third reason for these starting values is that they have been shown to lead to stable solutions across a range of sample sizes when they were used in a different multilevel multidimensional IRT model (Fujimoto, ).…”
Section: The Bayesian Correlated Multilevel Bifactor Irt Modelmentioning
confidence: 99%
“…These models, therefore, can be viewed as special cases of the multilevel multidimensional IRT modeling framework (Muthén & Asparouhov, ; Raudenbush, Johnson, & Sampson, ). There are many variations of dual‐dependent IRT models, such as those based on multilevel extensions of the cross‐classified structure (Jiao, Kamata, & Xie, ) and the trifactor structure (Fujimoto, ), but of particular interest for this study are the variations based on the multilevel bifactor structure (De Jong, Steenkamp, & Fox, ; Jiao et al., ; Jiao & Zhang, ; Wang, Kim, Dedrick, Ferron, & Tan, ). Thus, for the remainder of this article, dual‐dependent IRT models will refer to those versions based on a multilevel bifactor structure, with the multilevel portion consisting of the responses (Level 1) nested within persons (Level 2) and the persons nested within clusters (Level 3).…”
Section: A Conceptual Overview Of Dual‐dependent Irt Models' Assumptionsmentioning
confidence: 99%